Wakefield excitation and electron acceleration at detuning bunch repetition frequency and frequency of eigen principal mode of wakefield - Balakirev, V.A.; Onishchenko, I.N.; Tolstoluzhsky, A.P. (Вопросы атомной науки и техники, 2013)
Theoretical results of process of the wake field excitation in the dielectric waveguide by sequence of relativistic bunches in the presence of detuning between the bunch repetition frequency and the frequency of the fundamental wave waveguide. In this case the wake waves radiated by individual bunches, there is the phase shift, and, beginning with some number of the bunch, the phase shift will be. The polarity of the field is changed and the subsequent bunches gain energy. Energy spectra of accelerated (decelerated) particles are obtained. Викладено результати теоретичних досліджень процесу збудження кільватерного поля в діелектричному хвилеводі послідовністю релятивістських згустків при наявності розстройки між частотою проходження згустків і частотою основної хвилі хвилеводу. У цьому випадку для кільватерних хвиль, випромінюваних окремими згустками, виникає набіг фази і, починаючи з деякого номера згустку, набіг фази складе π . Змінюється полярність поля і наступні згустки набирають енергію. Отримані енергетичні спектри прискорених (уповільнених) частинок. Изложены результаты теоретических исследований процесса возбуждения кильватерного поля в диэлектрическом волноводе последовательностью релятивистских сгустков при наличии расстройки между частотой следования сгустков и частотой основной волны волновода. В этом случае для кильватерных волн, излучаемых отдельными сгустками, возникает набег фазы и, начиная с некоторого номера сгустка, набег фазы составит π . Изменяется полярность поля и последующие сгустки набирают энергию. Получены энергетические спектры ускоренных (замедленных) частиц.